2020
DOI: 10.1111/1750-3841.15007
|View full text |Cite
|
Sign up to set email alerts
|

Rate‐All‐That‐Apply (RATA) comparison of taste profiles for different sweeteners in black tea, chocolate milk, and natural yogurt

Abstract: Growing health concerns have increased interest in reducing the consumption of added sugars, which can be achieved by substituting or replacing sugar with sweeteners to maintain sensory intensity and quality. The growing availability of sweeteners has increased the complexity of the perceptual landscape as sweeteners differ in the qualitative, intensity, and temporal properties. A sweetener that can match the perceptual properties of sucrose in different food matrices is likely to have broad applications. In c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 46 publications
0
25
0
5
Order By: Relevance
“…In this same trial, the authors have also found changes in hormone levels, such as appetite-suppressing hormone PYY and hunger hormone ghrelin, and an increase in the eating rate during the ultra-processed diet [14]. In a more recent study based on pooled data from five previously published reports of food energy intake rates, ultra-processed foods had an energy intake rate twice as high as that observed among unprocessed foods (69.4 and 35.5 kcal/min, respectively) [28]. This can be explained by the oro-sensory properties of the ultra-processed foods (e.g.…”
Section: Discussionmentioning
confidence: 93%
“…In this same trial, the authors have also found changes in hormone levels, such as appetite-suppressing hormone PYY and hunger hormone ghrelin, and an increase in the eating rate during the ultra-processed diet [14]. In a more recent study based on pooled data from five previously published reports of food energy intake rates, ultra-processed foods had an energy intake rate twice as high as that observed among unprocessed foods (69.4 and 35.5 kcal/min, respectively) [28]. This can be explained by the oro-sensory properties of the ultra-processed foods (e.g.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, higher concentrations are perceived as being more intense and long lasting, with very little differences observed between scaling methods (Lawless & Skinner, 1979). When used in a matrix, sucrose retains its sweetness profile and has fewer cited side tastes as compared to synthetic or natural substitutes (Tan et al., 2020, Wagoner, McCain, Foegeding, & Drake, 2018). Thus, a successful sugar replacement must match the rapid rise and fall of sweetness, with the lack of additional side tastes characteristic of sucrose.…”
Section: Sensory Properties Of Synthetic and Natural Sweetenersmentioning
confidence: 99%
“…One means of reducing the sugar content in processed foods has been the use of low‐calorie sweeteners. It is widely accepted that aspartame, neotame, stevia, and sweetener blends play an important role in the sensory aspects of acceptance and consequently affect the consumers' hedonic response to yogurts (Hernández‐Morales, Hernández‐Montes, & Villegas‐de Gante, 2007; Kalicka, Znamirowska, Buniowska, Esteve Más, & Canoves, 2017; King, Arents, & Duineveld, 2003; King, Lawler, & Adams, 2005; Miele et al, 2017; Pinheiro, Oliveira, Penna, & Tamime, 2005; Tan, Wee, Tomic, & Forde, 2020). These substances deliver high levels of sweetness without increasing the caloric intake (Carocho, Morales, & Ferreira, 2017).…”
Section: Introductionmentioning
confidence: 99%